2016
DOI: 10.5530/jppcm.2016.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of Pharmaceuticals in Water as New Area in Eco-Pharmacovigilance Research

Abstract: Pharmaceuticals in water can have potential toxic effects on environment and human. It is becoming an emerging research area. Pharmaceuticals have received a growing attention from environmental and health agencies all over the world due to recent studies showing the occurrence of pharmaceutical compounds in environment, especially in water bodies and have become one of the emerging water pollutants. The aim of this review article is to study the hazards of pharmaceuticals in water reported in the literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Pharmaceuticals in the sewage system can be degraded or removed, however some residues remain and are present in very low concentrations in surface waters, WWTPs, in hospitals influent and effluent, and drinking water . Diclofenac, a non‐steroidal anti‐inflammatory drug, is one of the most extensively studied pharmaceuticals due to its potentially toxic effects and low biodegradability in WWTPs . Al‐Odaini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals in the sewage system can be degraded or removed, however some residues remain and are present in very low concentrations in surface waters, WWTPs, in hospitals influent and effluent, and drinking water . Diclofenac, a non‐steroidal anti‐inflammatory drug, is one of the most extensively studied pharmaceuticals due to its potentially toxic effects and low biodegradability in WWTPs . Al‐Odaini et al .…”
Section: Introductionmentioning
confidence: 99%
“…[12] Pharmacovigilance (PV) is defined by the WHO as the science and activities that relate to the detection, assessment, understanding and prevention of adverse effects of drugs or any other possible drug-related problems. [14] Thalidomide was named the greatest tragedy in 1961 and led to the establishment of the current drug regulatory mechanisms. Pharmacovigilance is defined as an arm of patient care that aims at taking advantage of the drugs and medicines to treat or prevent diseases without any unwanted effects.…”
Section: Introductionmentioning
confidence: 99%
“…All these are hazardous to patient safety, simultaneously putting people at the risk of fatality due to ADRs every single year. [14,15] Various studies were done to assess students' knowledge of pharmacovigilance and ADRs reporting, and their attitude towards them showed that there is a deficiency of knowledge concerning pharmacovigilance and ADR reporting. [16][17][18][19][20][21] Therefore the study objective is to assess and compare the knowledge, attitude and practice of pharmacovigilance and adverse drug reporting among final year Pharmacy, Dental and Medicine students in Aden University.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of pharmaceuticals in wastewater and environmental samples is highly dependent on local diseases, treatment habits and market profiles, thus, the pollution profile can vary significantly between different countries [12]. Pharmaceuticals in water can have potentially toxic effects on the environment and human [13]. However, pharmaceuticals are not included in the models for the assessment of water quality index [14, 15].…”
Section: Introductionmentioning
confidence: 99%